Development and characterization of extruded snack based on tapioca flour, and sensory evaluation on purchase intention (Research, Society and Development, 2021)
In this work, the objective was to develop an extruded snack type snack, adding tapioca flour from cassava to its main formulation. The characterization of the proximate composition of the products developed was carried out, moisture, proteins, lipids, ashes and carbohydrates were analyzed. Regarding physical characteristics, analyzes were carried out such as apparent density, specific volume, retraction index calculated in relation to forty days and expansion index, expansion index, specific volume, apparent density, retraction index, water activity (Aw), index water absorption (IAA) and water solubility index (ISA) and instrumental color. For the sensory analysis, attributes such as appearance, aroma, flavor, texture and overall impression were analyzed. After carrying out the analyzes, the best formulation for extrusion in the raw material extruder tapioca flour with 16% moisture content was identified, referring both to its physical characteristics and its composition. In general, all samples analyzed in the applied sensory test and purchase intention were satisfactorily accepted by the tasters. This study demonstrated that the raw material tapioca flour with a moisture content of 16% showed the best results in the extrusion process in mono-screw extruder in its development.